A qualitative study on the perspectives and needs of oncology nurses about recognition and management of suicide risk in cancer patients. Issue 5 (27th March 2022) - Öztürk, Sevda; Hiçdurmaz, Duygu
Abstract: Aims: To determine the perspectives and needs of the oncology nurses in recognising and managing the risk of suicide in cancer patients. Background: Cancer patients are one of the groups with a high risk of suicide. The perspectives and needs of oncology nurses regarding their recognition and management of suicide risk in such patients need to be clarified. Design and methods: This qualitative descriptive study used a sample of 33 oncology nurses that were sampled by maximum variation sampling from different oncology units and hospitals. Data were collected with in‐depth interviews via a semi‐structured interview form and analysed with content analysis. The COREQ guideline was followed for the reporting of the study. Results: Three main themes and eight subthemes were identified, namely 'An uncertain atmosphere: sensing the risk of suicide but not seeing the picture' (Subthemes: Inability to identify suicide risk, Unclear responsibilities and Distress as a result of uncertainty), 'Efforts to give meaning to and compensate losses of patients' (Subthemes: Attributions to cancer‐related losses of patients and Interventions to alleviate distress related to loss) and 'Hindrances beyond the nurse' (Subthemes: Stigma towards psychosocial problems and getting help, Disagreement with the Physician and A lack of institutional culture on suicide prevention). Conclusions: Our study revealed that oncology nurses have insufficient knowledge and skills and unclear roles in recognising and managing suicide risk. In addition, nurses have difficulty in helping patients due to the insufficient support of team members, stigmas of patients and their relatives towards getting help, patient workloads, and inadequate institutional support in risk management. Training programmes aiming to increase nurses' awareness, knowledge and skills should be developed and embedded into current in‐service education programmes and undergraduate education curricula as part of professional improvement. Relevance to clinical practice: The results of the study can contribute to planning the content and scope of suicide prevention training peculiar to oncology nursing.